Debunking the Myth of “Corporate Slaves” Among Generation Z Through the Lyrics of Hindia’s Song “Just Dance—This Career Has No Meaning” - Poetra Raqhib Indayanto; Nurliah; Dony Kristian; Harry Isra Muhammad (CV. Publikasi Indonesia, 2026)
The emergence of Generation Z in the modern workplace has introduced new perspectives on career values, work-life balance, and professional identity. The dominant narrative that equates personal success with productivity, career achievement, and organizational loyalty has created psychological pressures among young workers, often represented through the concept of the “corporate slave.” This study aimed to examine how the myth of corporate slavery among Generation Z was deconstructed through the lyrics of Hindia’s song “Berdansalah, Karir Ini Tak Ada Artinya” using Roland Barthes’ semiotic perspective. This research employed a qualitative descriptive approach with textual analysis as the primary method. The primary data consisted of the song lyrics, while secondary data were obtained from relevant academic literature. Data analysis focused on three levels of Barthes’ semiotics: denotation, connotation, and myth. The findings revealed that the lyrics represented workplace anxiety, emotional exhaustion, and resistance toward excessive career-oriented values. At the denotative level, the song portrayed everyday experiences of workers seeking freedom from rigid work routines. At the connotative level, these expressions symbolized forms of everyday resistance against dehumanizing work cultures. At the mythical level, the song challenged the ideology that career achievement determines human worth and offered an alternative narrative emphasizing freedom, authenticity, and self-constructed meaning. The study concluded that Hindia’s song functioned not only as an artistic expression but also as a medium of symbolic resistance reflecting Generation Z’s struggle to redefine success and personal freedom in contemporary society.